Implementation and application of automata 16th international conference, CIAA 2011, Blois, France, July 13-16, 2011. proceedings - Bouchou-Markhoff, Béatrice (Lecture notes in computer science, 2011)
This book constitutes the thoroughly refereed papers of the 16th International Conference on Implementation and Application of Automata, CIAA 2011, held in Blois, France, in July 2011.The 20 revised full papers together with 4 short papers were carefully selected from 38 submissions. The papers cover various topics such as applications of automata in computer-aided verification; natural language processing; pattern matching, data storage and retrieval; document engineering and bioinformatics as well as foundational work on automata theory.